Mapping of faults in the Libyan Sirte Basin by magnetic surveys - Saheel .A.S,; Abdul Rahim Samsudin,; Umar Hamzah, (Universiti Kebangsaan Malaysia, 2011)
Magnetic surveys were carried out in Farigh area which is located in the eastern part of the Libyan Sirte basin. Interpretation of the onshore magnetic anomaly of this area, suggests that the high total magnetization may be caused by an intrusive body. Analysis of the magnetic power spectra indicates the presence of four sub-anomalies at depths of 340 m, 1400 m, and 2525 m which is probably related to the igneous rocks. The presence of igneous rock as basement at depth of 4740 m was confirmed by drilling. Assuming that all rock magnetization in the area is caused by induction in the present geomagnetic field, it strongly suggests that the causative structure has a remnant magnetization of declination (D) = −16° and inclination (I) = 23°. Based on pseudogravity data, the total horizontal derivative map shows high gradient values in NW-SW trends related to the structures in the eastern part of the Sirte basin. The 3D Euler deconvolution map derived from gravity data clearly indicates the location of igneous body in the study area as well as its tectonic trends and depth, which is estimated at 350 m to 1400 m below the surface. Depth of gravity anomalies at 1400 m to 2525 m is considered as anomalies in between shallow and deep. Anomaly at depth of approximately 4740 m below the surface is interpreted as basement rock. Geologically, the magnetic survey shows that the source of anomaly is a mafic igneous rock of Early Cretaceous age. The study also discovered a left-lateral sheared fault zone along the NW-SE of Hercynian age which was believed to be reactivated during Early Cretaceous